2014
DOI: 10.1007/s10585-014-9665-2
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 in primary tumors promotes melanoma dissemination

Abstract: Metastatic melanoma is one of the most aggressive forms of skin cancer and has a poor prognosis. We have previously identified Annexin A1 (ANXA1) as a potential murine melanoma-spreading factor that may modulate cell invasion by binding to formyl peptide receptors (FPRs). Here, we report that (1) in a B16Bl6 spontaneous metastasis model, a siRNA-induced decrease in tumoral ANXA1 expression significantly reduced tumoral MMP2 activity and number of lung metastases; (2) in a retrospective study of 61 patients, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…Previous reports suggest that ANXA1 is involved in membrane aggregation, cell matrix interaction, vesicle transport, phagocytosis, proliferation, apoptosis, inflammation and cell transformation29. ANXA1 expression is up-regulated in breast cancer30, hepatocellular carcinoma31, melanoma32, and rectal cancer, but down regulated in nasopharyngeal carcinoma33 and cervical cancer34. In breast cancer, ANXA1 expression is associated with BRCA1/2 mutations35.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that ANXA1 is involved in membrane aggregation, cell matrix interaction, vesicle transport, phagocytosis, proliferation, apoptosis, inflammation and cell transformation29. ANXA1 expression is up-regulated in breast cancer30, hepatocellular carcinoma31, melanoma32, and rectal cancer, but down regulated in nasopharyngeal carcinoma33 and cervical cancer34. In breast cancer, ANXA1 expression is associated with BRCA1/2 mutations35.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that ANXA1 may function as either a negative or a positive regulator of malignant phenotypes of various cancer cells. For example, downregulation of ANXA1 expression with specific ANXA1 siRNA in human breast cancer cell line MDA-MB-231 led to decreased cancer cell migration and invasion [10]; Ang et al [25] observed that silencing of ANXA1 with specific ANXA1 siRNA could reverse the estrogen-dependent proliferation as well as growth arrest of MCF-7 breast cancer cells; Boudhraa et al [9] reported that in a B16Bl6 spontaneous metastasis model, a siRNAinduced decrease in tumoral ANXA1 expression significantly reduced tumoral MMP2 activity and number of lung metastases, and in human melanoma cell lines, ANXA1 Fig. 3 Relative expression of annexin A1 (ANXA1) protein in hepatocellular carcinoma (HCC) cell lines HepG2 and BEL-7402 transfected with ANXA1 siRNA (si-ANXA1) and negative control siRNA (si-con).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggest that it contributes to the pathological consequence and sequelae of most serious human diseases, including cancers. As a potential marker for malignant progression, ANXA1 expression levels have been observed to be upregulated in melanoma, breast cancer, pancreatic cancer, and colorectal cancer [9][10][11][12][13]. In contrast, reduced ANXA1 expression levels have been found in esophageal cancer, gastric cancer, bile duct cancer, and prostate cancer [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A increasing number of studies suggested that the expression and the function of ANXA1 in tumors are tissue-and tumor-specific (9,10). Upregulation of ANXA1 was observed in human breast cancer (11), hepatocellular carcinoma (12) and melanoma (13,14), whereas downregulation of ANXA1 was observed in gastric cancer (15), prostate cancer (16,17) and oral cancer (18,19). The function of ANXA1 in tumors appears to be paradoxical.…”
Section: Introductionmentioning
confidence: 99%